Prophetic Intelligence in Islamic Education for Corruption Prevention: A Study from Solo Raya within the SDGs Framework - Muh. Fatahillah Suparman; Sujito; Moh. Abdul Kholiq Hasan; Al-Ameen M. Ibnohajad; Eman Suherman (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study aims to analyze the implementation of prophetic intelligence in Islamic education as a strategy for building anti-corruption character in the Greater Solo area, by highlighting its contribution to the achievement of Islam and the SDGs. Theoretical framework: The theoretical framework of this research is based on the concept of prophetic intelligence that combines rationality, spirituality, and morality as the basis of ethical awareness. Literature review: Literature review confirms that prophetic Islamic education plays an important role in instilling ethical and spiritual values as a measure to prevent corruption. Several studies have shown that the integration of prophetic values in the Islamic education curriculum can form a culture of honesty, social responsibility, and institutional transparency. Methods: This study uses a qualitative approach with phenomenological methods to explore the meaning of teachers' experiences in implementing prophetic values in Islamic educational institutions in Solo Raya. Data was obtained through in-depth interviews, participatory observations, and documentation studies, then analyzed with Miles and Huberman's interactive model that included data reduction, presentation, and verification. Results: The results of the study show that the implementation of prophetic intelligence is effective in strengthening integrity, honesty, and accountability in the educational environment. Teachers act as an ethical bridge between spirituality and modern governance, internalizing prophetic values through example, moral habituation, and ethical reflection. Prophetic Islamic education has been proven to be able to suppress corrupt behavior and foster a culture of social responsibility. Implications: The integration of prophetic values in Islamic education has a direct impact on the establishment of educational institutions that are transparent, ethical, and just, as well as serving as a moral model for the wider community. Novelty: This study examines applying prophetic intelligence in Islamic education as an anti-corruption character strategy by integrating prophetic values into curricula, linking it to SDG 4 and SDG 16 an area still underexplored.